Health literacy in elderly in Northern Norway- association with socioeconomic status and general health/oral health - Thoresen, Therese (Universitetet i Tromsø, 2013)
Objective: The aim of this study was to investigate whether oral health and health literacy are associated which diseases, medication, self- reported health/oral health and socioeconomic factors in a group of people ranging from 50 to 80 years of age. Materials and methods: The study consisted of 61 patients, 27 men (52-78 years; M=61.6 years) and 34 women (51-80 years; M=61.0 years). They had oral examination including dentition status by DMFT (decayed, missed, filled teeth), plaque index, gingival index and stimulated saliva sampling. A questionnaire was completed regarding demographic and social status, educational level, as well as self-reported health and self-reported oral health. Health literacy level where assessed by utilizing the Adult Health Literacy Instrument for Dentistry (AHLID). Results: By using multiple regression analyses we found an association between health literacy and the use of medication. Furthermore, there are also associations between self- reported health, and income. Conclusion: We can confirm earlier studies that those with low health literacy level tend to be more ill and that those with higher self-reported health have higher levels of education and income. Consequently, we find it important to establish the literacy level and other relevant factors for every patient in order to provide the best treatment for each individual. Thus, we interpret our result that it is important to know a person’s literacy level, and consider complex factors to be sure that each individual get information regarding own oral health, and can understand, interpret and act in a correct way.